Ayo berdoa sebelum tidur=Lets prag before we sleep Rofatul Athfal ; ilustrator, Aldriana A. Amir ; editor, Kiki Sulisyani, Setya Bhawono, M.H. Eddy - ATHFAH, Rofatul; Amir, Adriana A; Sulistyani, Kiki; Bhawono, Setya; Eddy, M.H (Erlangga, 2006)
39 hlm. : ilus. ; 28x222 cm.